Visualizing mobile phone usage for exploratory analysis: A case study of Portugal - Kaewnoi N. (2017)
© 2016 ACM. This paper presents a visualization tool for mobile phone usage analysis. Data of mobile phone usage from Portugal is used for demonstration. The visualization runs on two modes: Flow and Intensity. Flow mode displays a 3D animation of mobile phone usage, showing the communication flows between municipalities. Intensity mode displays a 3D animation of the intensity level (amount of mobile phone usage) per cellular tower aggregated every 30 minutes. The tool also allows the user to interact with it by not only selecting different modes of display, but also visualizing data of any selected municipality. The visualization gives an overview of the dynamic communication flows, which helps describe mobile phone usage characteristics and social behavior. It can also be useful for telecom operators for better informed planning and management, as well as for urban planners and researchers for exploratory behavioral analysis.